Numerical study of dry snow accretion characteristics on the bogie surfaces of a high-speed train based on the snow deposition model. Issue 3 (4th May 2022) - Cai, Lu; Lou, Zhen; Li, Tian; Zhang, Jiye
ABSTRACT: To investigate the distribution of dry snow particles deposited on the bogie surfaces of a high-speed train, a snow particle deposition model based on the critical capture velocity and the critical wind friction speed was established. The suspension motion behaviour of snow particles in the air was simulated by the unsteady Reynolds-averaged Navier–Stokes (uRANS) simulations, based on the Realizable k–ε turbulence model and the Discrete Phase Model (DPM). The results show that the crossbeam of the bogie frame, the anti-snake movement dampers, the middle brake shoes of the rear brake rigging, the traction rods and the anti-rolling torsion bars are prone to accumulating snow. Furthermore, the critical capture velocity has a significant effect on the distribution of snow accretion. When the critical capture velocity is changed from 1.0 m/s to 3.0 m/s, the total snow accumulation on the bogie will increases by 20%.